ENGLISH SPEAKING CONFIDENCE AMONG FLOOD-AFFECTED ELEMENTARY SCHOOL STUDENTS - Suci Rahmi Amjusfa; Yawma Wulida; Rafni Fajriati; Rahmatul Ukhra (JOURNAL OF EDUCATION SCIENCE, 2026)
This study aimed to describe the level of English speaking confidence among flood-affected elementary school students in Pidie Jaya Regency. Speaking confidence was considered a crucial affective factor influencing young learners’ success in learning English, particularly for students who experienced emotional disruption due to natural disasters. This research employed a descriptive quantitative design. The participants consisted of 35 flood-affected elementary school students who were selected using a total sampling technique. Data were collected through an English speaking confidence questionnaire developed using a four-point Likert scale, which covered aspects of willingness to speak, fear of making mistakes, self-confidence, and participation in English learning activities. The collected data were analyzed using descriptive statistics in the form of mean scores and percentages. The findings revealed that the overall level of students’ English speaking confidence was categorized as moderate, with a total mean score of 2.89. Classroom participation obtained the highest mean score, while fear of making mistakes showed the lowest mean score. These results indicated that although students demonstrated engagement in English learning activities, affective barriers remained a challenge in post-disaster learning contexts. Therefore, greater attention to emotional support and low-anxiety speaking activities was needed in English instruction for flood-affected elementary school students.